Demarcating exercise intensity domains in freestyle swimming: is there an alternative to incremental step test and beats below HRmax method? - Piatrikova, E.; Sousa, A. C.; Willsmer, N. J.; Gonzalez, J. T.; Williams, S. (The Journal of Strength and Conditioning Research, 2020)
Critical power derived from the 3-minute all-out test (3MT) was recently used to estimate the exercise intensity boundaries in competitive cyclists. Considering that physiological testing is challenging in swimming, the purpose of this study was to examine whether critical speed (CS) derived from the 3MT could be used for the same purpose in swimming. The second aim was to assess the accuracy of the 50-40 and 30-20 beats below the maximal (BBM) heart rate method, currently used by swimming coaches to demarcate boundaries between moderate-heavy and heavy-severe exercise, respectively. Thirteen swimmers completed an incremental step test (IST) and 3MT in freestyle to establish speeds at: lactate threshold (LT), lactate turnpoint (LTP), maximum aerobic speed (Smax), and CS. Using linear regression through origin, speeds at LT, LTP, and Smax were predicted at 89, 98, and 104% of CS derived from the 3MT, respectively. There were no significant differences between threshold speeds derived from the IST and 3MT (p > 0.05), and nearly perfect correlations at LT (1.21 ± 0.06; 1.21 ± 0.06 m/s; r = 0.92) and LTP (1.33 ± 0.07; 1.33 ± 0.07 m/s; r = 0.90), and very large correlations at Smax (1.40 ± 0.06; 1.40 ± 0.07 m/s; r = 0.88; all p < 0.0001). Speeds estimated at 50 (1.11 ± 0.08 m/s) and 40 BBM (1.17 ± 0.07 m/s) were lower compared with LT, and speeds estimated at 30 (1.23 ± 0.07 m/s) and 20 BBM (1.29 ± 0.07 m/s) were lower compared with LTP and CS (all p < 0.02). The 3MT can therefore be used as an alternative to the IST to estimate exercise intensity boundaries, in practical settings where resources or time might be limited. However, the BBM significantly underestimates speeds at LT, LTP, and CS.